Prices and quantities in the monetary policy transmission mechanism - Tobias Adrian; Hyun Song Shin (Federal Reserve Bank of New York, 2009)
Central banks have a variety of tools for implementing monetary policy, but the tool that has received the most attention in the literature has been the overnight interest rate. The financial crisis that erupted in the summer of 2007 has refocused attention on other channels of monetary policy, notably the transmission of policy through the supply of credit and overall conditions in the capital markets. In 2008, the Federal Reserve put into place various lender-of-last-resort programs under section 13(3) of the Federal Reserve Act in order to cushion the strains on financial intermediaries' balance sheets and thereby target the unusually wide spreads in a variety of credit markets. While classic monetary policy targets a price (for example, the federal funds rate), the liquidity facilities affect balance-sheet quantities. The financial crisis forcefully demonstrated that the collapse of the financial sector's balance-sheet capacity can have powerful adverse effects on the real economy. We reexamine the distinctions between prices and quantities in monetary policy transmission.
Keywords: E52; E59; E02; 330; Monetary policy; liquidity facilities